KOMUNIKASI ORANG TUA UNTUK MENGURANGI KETIDAKPASTIAN PADA ANAK RETARDASI MENTAL - Allien Mai Dianna; Nuriyatul Lailiyah (Jurusan Ilmu Komunikasi, FISIP, Universitas Diponegoro, 2019)
The purpose of this study is to describe the parental communication to reduce the uncertainty in mental retardation children. The method that used in this study is qualitative research with phenomenological approaches. The theory that used is Uncertainty Reduction Theory. The research found that the experience of communication uncertainty that experienced by parents occurs when they have to deliver a message, such as teaching something or giving an understanding of a certain condition because their children tend to be slow processing and don't care about the parents condition. Other than that, the uncertainty increases because parents can’t know for certain what the children’s thinking. Parents with mild mental retardation children have a tendency to treat their children as same as normal children because the lack of visible difference, while parents with moderate mental retardation can put themselves in a better position. Even so, parents keep accepting whatever the condition and hoping that their child can develop even better. 2 The emotional closeness and self disclosure that intertwined also giving a part to affect how the development of the relationship between parents and child. Parents who are closer and open to children have a warm and close relationship than those who don’t. The parents realize this things makes the uncertainty that arises when interacting can be managed well and create an effective communication because children do the reciprocity. With it, parents can understand better the children with mental retardation.